2017
DOI: 10.1016/j.neuroimage.2017.01.030
|View full text |Cite
|
Sign up to set email alerts
|

EEG neural correlates of goal-directed movement intention

Abstract: Using low-frequency time-domain electroencephalographic (EEG) signals we show, for the same type of upper limb movement, that goal-directed movements have different neural correlates than movements without a particular goal. In a reach-and-touch task, we explored the differences in the movement-related cortical potentials (MRCPs) between goal-directed and non-goal-directed movements. We evaluated if the detection of movement intention was influenced by the goal-directedness of the movement. In a single-trial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 54 publications
3
78
0
Order By: Relevance
“…These results are similar to some researches available in the literature [4,10,15]. The research conducted by Jochumensen et al [15] in 2015 aimed at detecting movement intention of palmar grasp with different force levels and duration.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These results are similar to some researches available in the literature [4,10,15]. The research conducted by Jochumensen et al [15] in 2015 aimed at detecting movement intention of palmar grasp with different force levels and duration.…”
Section: Discussionsupporting
confidence: 88%
“…However, in this study, the classifier was trained to identify the "relax" and "movement" screening trials, but not to differentiate movements. Pereira et al performed a research in 2017 [10] to evaluate the movement intention in different conditions: goal, no-goal, movement and no-movement tasks. The average accuracy of all tasks was 67%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of neurophysiologically-driven hand prosthetics, hybrid brainmachine interfaces (hBMIs) based on fusion of electroencephalographic (EEG) and electromyographic (EMG) activities to decode upper limb movements gained significant interest [1], [2]. In that regard, to investigate neural correlates of human motor behavior, a variety of recent studies have shown promising results in both EEG-based [3][4][5][6][7][8] and EMGbased [9][10][11] settings for decoding of complex same hand gestures. In the light of recent promising work, we argue that probabilistic fusion of multimodal information sources in a unified framework would yield significant insights to develop robust hybrid BMIs for neural prosthetics.…”
Section: Introductionmentioning
confidence: 99%